PENGARUH MEDIA SPINNER TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PADA SISWA KELAS IV DI SD NEGERI 04 BELIDA DARAT - Yepi Sapitri; Ramanata Disurya; Juaidah Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low learning outcomes of students in Civic Education, particularly on the topic of rights and responsibilities. One of the causes is the lack of variety in the use of learning media that can enhance students’ interest and understanding. The aim of this study is to determine the influence of spinner media on the Civic Education learning outcomes of fourth-grade students at SD Negeri 04 Belida Darat. The research employed a quasi-experimental method with a post-test only control group design. Data were collected using a multiple-choice learning outcome test. The results showed that the average post-test scores of students in the experimental class using spinner media were higher than those in the control class using conventional methods. The t-test results indicated a significant difference between the learning outcomes of the two classes. Therefore, the use of spinner media has been proven to significantly influence the improvement of students’ learning outcomes in Civic Education. This suggests that spinner media can serve as an innovative and interactive alternative learning tool to enhance student achievement